2017
DOI: 10.1038/s41598-017-12632-9
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of adiponectin receptor 1 promotes memory dysfunction and Alzheimer’s disease-like pathologies

Abstract: Recent studies on neurodegeneration have focused on dysfunction of CNS energy metabolism as well as proteinopathies. Adiponectin (ADPN), an adipocyte-derived hormone, plays a major role in the regulation of insulin sensitivity and glucose homeostasis in peripheral organs via adiponectin receptors. In spite of accumulating evidence that adiponectin has neuroprotective properties, the underlying role of adiponectin receptors has not been illuminated. Here, using gene therapy-mediated suppression with shRNA, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 53 publications
5
39
0
Order By: Relevance
“…Some studies on metabolic diseases have reported that metabolic diseases, such as T2DM and obesity, are associated with AD. Metabolic alteration of substances such as T2DM-related insulin receptors [ 29 ] and obesity-related adiponectin [ 30 , 31 ] could alter the process of aging and age-related dementia, such as in AD. In a recent study, Nasoohi et al suggested the relationship of “type 3 diabetes” to AD pathology, in which the metabolic syndrome consisting of oxidative stress and neuroinflammation leads to brain insulin resistance [ 32 ].…”
Section: Relationship Between Metabolic Disorder and Alzheimer’s Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies on metabolic diseases have reported that metabolic diseases, such as T2DM and obesity, are associated with AD. Metabolic alteration of substances such as T2DM-related insulin receptors [ 29 ] and obesity-related adiponectin [ 30 , 31 ] could alter the process of aging and age-related dementia, such as in AD. In a recent study, Nasoohi et al suggested the relationship of “type 3 diabetes” to AD pathology, in which the metabolic syndrome consisting of oxidative stress and neuroinflammation leads to brain insulin resistance [ 32 ].…”
Section: Relationship Between Metabolic Disorder and Alzheimer’s Dmentioning
confidence: 99%
“…However, low levels of adiponectin in CSF may be compensated by the presence of two high-affinity receptors, AdipoR1 and AdipoR2, in the brain [ 64 , 65 ]. Suppression of AdipoR1 can result in metabolic diseases such as obesity and diabetes, which also potentiate spatial learning deficit, memory impairment, and AD pathologies [ 30 ]. Hence, studies have evaluated adiponectin and its receptors as therapeutic alternatives for AD.…”
Section: Adiponectin’s Potential Role In Alzheimer’s Diseasementioning
confidence: 99%
“…In detail, AdipoR1 knockdown mice exhibited metabolic abnormalities and failed to perform behavioural tests correctly. Moreover, AdipoR1 knockdown animals were found to have AD-like pathologies including insulin signalling dysfunction, abnormal protein aggregation, and neuroinflammatory responses similar to the brain pathologies observed in adiponectin-knockout mice [20].…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the group of Kim reported that AdipoR1 knockdown mice exhibited memory impairment and neuronal apoptosis, and these features were similar to those observed in the AD model. The authors concluded that AdipoR1 is an essential receptor for protecting against neuronal cell death and spatial and learning memory impairment [20]. Another group of researchers reported that in the APP/PS1 (amyloid precursor protein/presenilin 1) transgenic mice model of AD an altered expression of AdipoR1 and AdipoR2 in the hippocampus and the prefrontal cortex could be found [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been also recently shown in mice that APOE ε4 also affects tau pathogenesis and tau-mediated neurodegeneration independently of Aβ pathology [17]. On the contrary, the ε2 allele decreases the risk of developing the disease via protective effects against both late-onset and familial AD [18][19][20].…”
Section: Disease Classificationmentioning
confidence: 99%